Optimalisasi Pertumbuhan dan Hasil Seledri (Apium graveolens L.) melalui Aplikasi Pupuk Organik Cair Sabut Kelapa - Pebriani, Riska; Adnan, Adnan; Sondakh, Rian Christian (Permaculture: Jurnal Ilmu Pertanian & Lingkungan, 2025)
This study aimed to determine the effect of coconut husk liquid organic fertilizer (LOF) on the growth and yield of celery plants, as well as to identify the most effective concentration. The research was carried out in Tambun Village, Baolan District, Tolitoli Regency, from February 2025 to May 2025. The experiment was arranged in a Randomized Block Design (RBD) with a single factor consisting of five levels: P0 = Without organic fertilizer (Control), P1= LOF concentration of 50 ml/l water, P2= LOF concentration of 100 ml/l water, P3 = LOF concentration of 150 ml/l water, and P4 = LOF concentration of 200 ml/l water. Each treatment was replicated three times, resulting in 15 experimental units with a total of 75 plants. For each treatment, three sample plants were observed, giving a total of 45 observed samples. The results showed that the application of coconut husk LOF significantly affected celery (Apium graveolens L.) growth. The concentration of 200 ml/l water (P4) was the best treatment, consistently producing the highest values for plant height (17.97 cm at 6 weeks after planting), root volume (2.67 ml), and fresh weight (5.19 g). It was also observed that the higher the concentration of coconut husk LOF applied, the better the growth and yield of celery plants obtained.